The Identity of Justicia burkilliana (Acanthaceae) - Lin, Zhe-Li; Deng, Yun-Fei (Phytotaxa, 2017)
Examination of type materials revealed that Justicia burkilliana is conspecific with Rungia burmanica. A specimen at Herbarium K is selected as the lectotype for the name Justicia burmanica.